What is urban design? A proposal for a common understanding. Issue 1 (2nd January 2020) - Cozzolino, Stefano; Polívka, J.; Fox-Kämper, R.; Reimer, M.; Kummel, O.
ABSTRACT: The lack of a common understanding of what urban design is about is an issue that needs to be resolved. This paper analyzes some relevant contemporary definitions of urban design. Based on this analysis, it first identifies certain general features of this discipline. Then, it provides a general definition, and finally, it clarifies potential misunderstandings. In this paper, any discussion of what makes good urban design is avoided. The main goal is to provide a reasonable definition that can help to navigate the longstanding indeterminacy of this field.